Using mixed reality to support component restoration of Chinese traditional dwellings: A case study of column bases in Yanling House - Binghua Zhang; Yuze Dan (PLoS ONE, 2026)
Due to limited surveying, mapping, and image data, as well as technological constraints, current efforts to restore missing components in traditional Chinese dwellings often result in mismatches with the original appearance. This study employed a mixed-methods approach to evaluate the effectiveness of using mixed reality (MR) to address these challenges. Using an MR system built with Microsoft HoloLens 2 and Trimble Connect, we conducted an on-site experiment with twelve participants focused on column base restoration in the main hall of Yanling House, a typical traditional Chinese dwelling in Jintong Village, Youxi County, Fujian Province. Quantitative questionnaire ratings were utilized to illustrate the effects of MR in this on-site experiment, while qualitative semi-structured interviews provided further elucidation and validation of these effects. The results demonstrate that MR can help participants restore the components in a way that conforms to their original appearance through immersive perceptions, accurate adjustments, and convenient communications, thus providing effective technical support for preserving the unique historical and cultural value of traditional Chinese dwellings.